Vaccination Status and Awareness of Hepatitis B among Undergraduate Medical Students of Two Medical Colleges in Bangladesh (Medicine Today, 2017)
Hepatitis B is a pandemic disease affecting millions of people. Vaccination and preventive knowledge is crucial for all especially health care professionals. To evaluate the vaccination status and level of knowledge and awareness regarding hepatitis B among undergraduate medical students ranging from first to fifth year. This is a cross-sectional study which was conducted in Dhaka Medical College, Dhaka during July 2012 to July 2015. Total 217 students participated in the study (36.4% male and 63.6% female). Data was collected using a structured questionnaire. Statistical analysis was done using SPSS version 20. Most of the responders were female (63.6%) and from first year (31.3%). Only 41.4% were vaccinated properly and another 9.2% received incomplete doses. Those who had more knowledge regarding hepatitis B were practicing more preventive measures. The present study showed that there is much lack of knowledge and awareness about hepatitis B among medical college students that make them vulnerable to acquire the disease. Moreover, the vaccination status is also not satisfactory which should be taken seriously.Medicine Today 2016 Vol.28(1): 27-29